الضغوط النفسية و علاقتها بالصحة النفسية لدى المرأة المسنة بولاية الأغواط - عبد العزيز ايمان; جرادي فاطمة الزهراء البتول; عرعار سامية (My University, 2021)
The current study aims to reveal the nature of the relationship between psychological stress and mental health among a sample of elderly women in the state of Laghouat and some of its municipalities in the age group (60-87). The study also sought to find out the differences between variables such as age, social status, place of residence, educational level, health status and economic level. The number of boys in both psychological stress and mental health, and to achieve the objectives of the study, the psychological stress scale prepared by "Najla Ahmed Mubarak" 2015 and the modified mental health scale SCL-90-R was used to achieve the study objectives. Where the study was conducted on a sample of (80) elderly women, the statistical program (SPSS) in its version 25 was also used. The study resulted in the following results: 1- There is a relationship between psychological stress and mental health among elderly women 2- There are no statistically significant differences in psychological stress among elderly women due to the (age variable, variable of social status, the health status variable, to the economic level variable). 3- There are statistically significant differences in psychological stress among elderly women due to the educational level variable‌ج 4- There are no statistically significant differences in the mental health of elderly women due to the age variable, the variable of social status, the health status variable, the economic level variable 5- There are no statistically significant differences in the mental health of elderly women due to the educational level variable